2020
DOI: 10.4103/aer.aer_16_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of mcgrath MAC, Truview video laryngoscopes and Macintosh laryngoscope for endotracheal intubation in patients undergoing surgery under general anaesthesia

Abstract: Background: Videolaryngoscopy is a newly developed technique to improve tracheal intubation success. It was made to bypass the need of directly visualising the glottic inlet. These devices are advantageous as there is no need of aligning the laryngeal, pharyngeal and oral axes for a clear view, thus making intubation easier and faster. Aim and Objectives: Primary objective of the study was to determine the duration of laryngoscopy and intubation and Cormack - Lehane gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…restrictive inclusion criteria, for example limiting to experienced providers [5][6][7]; or patients with anticipated difficult airway [3][4][5]. Existing data on typical success rates of direct laryngoscopy in the operating theatre have similar limitations, with recent systematic reviews highlighting heterogeneity of such trials [1,2,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…restrictive inclusion criteria, for example limiting to experienced providers [5][6][7]; or patients with anticipated difficult airway [3][4][5]. Existing data on typical success rates of direct laryngoscopy in the operating theatre have similar limitations, with recent systematic reviews highlighting heterogeneity of such trials [1,2,6].…”
Section: Introductionmentioning
confidence: 99%
“…To date, numerous studies have compared videolaryngoscopy and direct laryngoscopy [1, 2]. Many of these studies have limitations that limit generalisability, such as small sample sizes [2–4]; restrictive inclusion criteria, for example limiting to experienced providers [5–7]; or patients with anticipated difficult airway [3–5]. Existing data on typical success rates of direct laryngoscopy in the operating theatre have similar limitations, with recent systematic reviews highlighting heterogeneity of such trials [1, 2, 6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaur et al have found that intubation was easy in Tuview group (87.50%) as compared to Macintosh group (65%). [ 14 ]…”
Section: Discussionmentioning
confidence: 99%